Le operazioni sul mercato di debito nel sistema finanziario islamico: il caso dei sukuk (Stato, Chiese e pluralismo confessionale, 2023)
Debt market transactions in the Islamic financial system:the case of sukukABSTRACT: In recent years, the secondary market for sukuk has been booming with growth rates ranging between 10-12%. In this paper we intend to analyze the structure of investment certificates that comply with the rules and economic principles of the Shari'ah. The markedly legal aspects of this instrument are therefore highlighted, first outlining the general structuring of Islamic certificates, and secondly, analyzing the operational profiles of the different types of sukuk most widespread on the Shari'ah compliant market. Finally, the guidelines issued by the Accounting and Auditing Organization for Islamic Financial Institutions on the subject are examined and the essential features of difference between the sukuk and conventional bonds are analyzed from a comparative point of view. The finale highlights the unexpressed potential of sukuk, recalling the best strategies for expanding Islamic investments. The primary objective is to raise the awareness of the relevant financial authorities, which appear disinterested in the Islamic financial market despite the resilience of this segment even during the Covid-19 pandemic.